Notes on the Recovery of the Coral Reef at Pescador Island, Off Moalboal, Cebu, Philippines, From Typhoon Damage - Alcala, Angel C.; Gomez, Edgardo D.; Alcala, Lawton C.; Luchavez, Teodulo (Silliman Journal, 2024)
Typhoon Nitang virtually decimated the live corals on the reef flat at Pescador Island on 2 September 1984. About a year later, the bare rocky substrate had shown little recovery in terms of area covered by live corals.